European Integration and Competitiveness of EU New Member States (European Journal of Marketing and Economics, 2026)
This research is intended to evaluate the influence of the European integration, through the EU financing dimension, upon the evolution of external competitiveness of countries part of the EU community since the enlargements of 2004 and, respectively, 2007, excluding Malta and Cyprus (hereafter called as New Member States (NMS)).  The paper methodology is based on appropriate research of relevant economic indicators intended to evaluate the EU funds’ influence on the industrial development and external competitiveness of NMS. Therefore, in the analysis performed there were figured out and calculated correlations between the following indicators: EU expenditure by NMS, Current Account to GDP ratio, Industrial Performance index, Global Innovation Index and Index of Economic Freedom. These indicators characterize the NMS’ business environment, institutional framework and, consequently, the degree of international competitiveness. The research contributes to confirm the assumptions about  the European integration and the EU financing instruments had important effects in improving the industrial performance, in particular, and international competitiveness of NMS, in general. However, the differences in the correlations calculated between EU financing received by the NMS and different analysed indicators, suggest that EU funds were not the only drivers of the increasing competitiveness of the analyzed countries.
Keywords: EU financing, Competitiveness, Industrial performance, Innovation.